Right to assemble peacefully under Article 10 of the federal constitution / Mazita Mohamed ... [et al.] - Mohamed, Mazita; Mohd Anuar, Haslinda; Ahmad, Rusniah; Mohd Ali@Ramli, Azlin Namili; Abdul Rahman, Rohana; Bidin, Muhammad Firdaus; Azmi, Ahmad Mohsein (2014)
Article 20(1) of Universal Declaration of Human Rights and Article 21 of International Covenant on Civil and Political Rights provide that everyone has the right to freedom of peaceful assembly. In Malaysia, such provision is stipulated under Article 10 of the Federal Constitution which combines the freedom of speech, peaceful assembly and association. However, these freedoms have restrictions which are usually justified under the broad stroke of maintaining racial harmony and public order. Prior to 23 April 2012, section 27 of the Police Act 1967 was implemented to govern a public assembly. After that date, the Peaceful Assembly Act 2012 became enforceable. It seeks to strike a balance between acknowledging the individual’s right to assemble peacefully as a fundamental human right and maintaining security and public order. The objective of this paper is to discuss the provisions under the Peaceful Assembly Act 2012 (Act 736) that are said to have embraced the spirit of Article 10 of the Federal Constitution. A critical comparison will be also made with section 27 of the Police Act 1967. Recommendations will also be pointed out, where necessary, in order to enhance the application of the present Act 736.